CNBC – Business News / CNBC – Business Tonight
CNBC news report on the dispute between George Soros and Malaysian Prime Minister Mahathir Mohamad who blamed George Soros for the Asian currency crisis that was emerging in 1997. It includes a fragment of Mahathir Mohamad’s speech in August, 1997, and George Soros’s speech at the World Bank Meeting in Hong Kong, on September 20, 1997. Other topics covered in the business magazine include: China, political reform, and stability; Thailand economy and IMF rescue package; U.S. bonds and currency; G7 meeting, trade deficits, and depreciation; Indonesia’s trade market and banking sector; corruption scandal in South Korea; voting in Philippines; banks and stock market in Asia; World Bank/IMF Meeting; bankers unofficial meetings. The programs feature excerpts of speeches and interviews with: Zhu Rongji (Vice-Premier of China), Joseph Stiglitz (Chief Economist, World Bank), Soedradjad Djiwandono (Governor of Bank Indonesia), Winthrop Smith (Chairman, Merrill Lynch International), Bernardo Pardo (Chairman, Comelec), and David McWilliams (Senior Economist, BNP United Kingdom).